Bajitianwan attenuates D-galactose-induced memory impairment and bone loss through suppression of oxidative stress in aging rat model. (28th October 2020) - Xu, Wumu; Liu, Xiaoyan; He, Xuhui; Jiang, Yiping; Zhang, Jiabao; Zhang, Qiaoyan; Wang, Nani; Qin, Luping; Xin, Hailiang
Abstract: Ethnopharmacological relevance: Osteoporosis and Alzheimer's disease (AD) are both senile diseases, which are closely related to oxidative stress. Bajitianwan (BJTW) is a classic Chinese formulation consisting of seven herbal drugs: the root of Morinda officinalis F.C.How., root and rhizome of Acorus tatarinowii Schott, the root bark of Lycium chinense Mill., the sclerotium of Poria cocos (Schw.) Wolf, the root of Polygala tenuifolia Willd., sclerotium with host wood of Poria cocos (Schw.) Wolf and root and rhizome of Panax ginseng C. A. Mey. BJTW has been used for the treatment of osteoporosis and AD for hundreds of years. Aim of the study: This study aimed to investigate the protective effects of BJTW in the amelioration of memory impairment and bone loss induced by D-galactose and to explore the underlying mechanism. Materials and methods: The aging model was established in male Wistar rats by subcutaneous injection of D-galactose (100 mg/kg), and the rats were treated with huperzine-A, alendronate sodium, or the aqueous extract of BJTW for 4 months. Cognitive performance was evaluated with the Morris water maze. Rat femurs were scanned using microcomputed tomography to obtain three-dimensional imagery of bone microstructure. The impact of D-galactose on the expression of Forkhead box O1 and superoxide dismutase 2 in femur tissue was also evaluated. Results: For the model group, BJTW treatment significantly reduced the latency time for finding the target platform in the directional swimming test and increased time spent swimming in the target quadrant with the probe test. Additionally, BJTW treatment alleviated D-galactose-induced bone loss through regulation of levels of alkaline phosphatase, osteocalcin, osteoprotegerin, and receptor activator of nuclear factor kappa B ligand. Furthermore, BJTW treatment increased catalase and glutathione peroxidase levels in serum, reduced malondialdehyde content in hippocampus, and upregulated expression of Forkhead O1, which upregulated superoxide dismutase 2 in the femur. Conclusions: BJTW had positive effects on age-related memory impairments and bone loss. It may be a promising antioxidant candidate for treatment of Alzheimer's disease and osteoporosis. Graphical abstract: Image 1